Front Cover: The Quantum Condition Space (Adv. Quantum Technol. 4/2022). Issue 4 (7th April 2022) - Hu, Zixuan; Kais, Sabre
Abstract : The cover image represents an artistic impression of the quantum circuit setup as proposed in article number 2100158 by Zixuan Hu and Sabre Kais, that can physically realize quantum conditions. The quantum condition space offers a novel perspective of understanding qubit‐based quantum states with the duality picture. The quantum conditions have physical meanings and realizations of their own and may lead to deeper understanding of the complexity of quantum circuits. (Image created by Yanan Huai)